УЛС ТӨРИЙН НАМУУДЫН ПРАГМАТИК ХАНДЛАГА - Ц.Батболд (Politology, 2023)
The article is mentioned about non ideology of political parties in academic level. The origins of political parties are based on saving the idealism of social grups interest. Here is shortly mentioned about ideology and political party’s activities. There is token a note about differences of some modern ideological categories and their value. Although, ideological comments to define equal right is clearly shown in the social scale and group standards. This case has defined the base of idealism and materialism. A modern ideological trend has developed with those 4 factors under bellowed. First: To take into consideration on average voter’s desire. Second: process to take into consideration on typical value of democracy is taken as important by any political parties. Third: purpose to national renewal makes close to ideologies due to recognizing the factors of some political party’s certain condition. Fourth: globalism, during the period of information era, political parties forced to abide united attitude for reason of accepting international legislation, right and rules, information wave and coordinating, local right to overcome and existing. Fifth: economical liberalization in worldwide, make a one’s goal in the market competition, there is a part to saving the monopole status, another part coordinate to reach at their standard, a third part to find and set up their own attitude in world market. There is a requirement for ideology of any country’s political parties concentrate in one certain direction. Modern social different ideology has lost the importance. There is some reasons of influence are under bellowed: the process of nationalism and globalization requires political parties to work pragmatic. Although, political parties more considered about reflect on what average voters idea are. In those factors, the common purpose is to direct the state by political parties. This is a condition of having few certain symbol monopole parties in society.